Impact of opioid dose escalation on pain intensity: a retrospective cohort study. Issue 5 (May 2020) - Hayes, Corey J.; Krebs, Erin E.; Hudson, Teresa; Brown, Joshua; Li, Chenghui; Martin, Bradley C.
Abstract : Abstract: Prescribers are often confronted with the decision to escalate opioid doses to achieve adequate analgesia. Understanding the impact of dose escalation on pain intensity is warranted. Using a retrospective cohort study design, Veterans with chronic pain and chronic opioid therapy were identified. Opioid dose escalators (>20% increase in average morphine milligram equivalent daily dose) were compared with dose maintainers (±20% change in average morphine milligram equivalent daily dose) assessed over 2 consecutive 6-month windows. Pain intensity was measured by the Numeric Rating Scale. The primary analyses used linear repeated-measures models among a 1:1 matched sample of escalators and maintainers matched on propensity score and within ±180 days of the index date. Sensitivity analyses were conducted using adjusted linear repeated-measures models with and without incorporating stabilized inverse probability of treatment weighting. There were 32, 420 dose maintainers and 20, 767 dose escalators identified with 19, 358 (93%) matched pairs. Pain scores were persistently higher among dose escalators at each 90-day period after the index date (0-90 days after index date: dose escalators: 4.68, 95% confidence interval [CI]: 4.64-4.72 dose maintainers: 4.32, 95% CI: 4.28-4.36, P < 0.0001; 91-180 days after index date: dose escalators: 4.53, 95% CI: 4.49-4.57; dose maintainers: 4.25, 95% CI: 4.22-4.29, P < 0.0001) but were not different in the 90 days before the index date (dose escalators: 4.64, 95% CI: 4.61-4.68; dose maintainers: 4.59, 95% CI: 4.55-4.63, P = 0.0551). Sensitivity analyses provided similar results as the primary analyses. Opioid dose escalation among patients with chronic pain is not associated with improvements in Numeric Rating Scale pain scores. Abstract : Supplemental Digital Content is Available in the Text.Increases in opioid dose of 20% or greater were not associated with improvements in pain scores. Clinicians should evaluate the need for increasing opioid doses.